2017
DOI: 10.18061/emr.v12i1-2.5833
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Tonal Stability and Metrical Accent in Monophonic Contexts

Abstract: Recent corpus analyses have provided evidence for interactions between tonal and metric hierarchies by illustrating that tonally stable pitches occur disproportionately often on strong metrical positions while tonally unstable pitches occur more frequently on weaker metrical positions. This study begins to investigate whether this observed property is salient to listeners' identification of metrical accents: by presenting participants with tonally-determined but metrically ambiguous beat patterns, we ask how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Supporting Schenker's ideas, their work revealed hierarchical organization as the driving factor, understanding the relationship between pitches, keys of tonal hierarchy and rhythmic structure as a way to understand tonal music's structure and processes. The claims made from GTTM are supported by empirical studies, all of which emphasizes the importance of tonal hierarchies, the close relationship between metric-rhythmic and pitch structure, and the combination of structure and hierarchical relationships to represent stability (Bharucha & Krumhansl, 1983;Bigand, 1990;Dibben, 1994;Krumhansl, 1979;Krumhansl & Kessler, 1982;Palmer & Krumhansl, 1987;White, 2017). These findings have also revealed the close relationship between such hierarchies to the notion of tension and release (Bigand, 1993;.…”
Section: Tonal and Atonal Tensionmentioning
confidence: 73%
“…Supporting Schenker's ideas, their work revealed hierarchical organization as the driving factor, understanding the relationship between pitches, keys of tonal hierarchy and rhythmic structure as a way to understand tonal music's structure and processes. The claims made from GTTM are supported by empirical studies, all of which emphasizes the importance of tonal hierarchies, the close relationship between metric-rhythmic and pitch structure, and the combination of structure and hierarchical relationships to represent stability (Bharucha & Krumhansl, 1983;Bigand, 1990;Dibben, 1994;Krumhansl, 1979;Krumhansl & Kessler, 1982;Palmer & Krumhansl, 1987;White, 2017). These findings have also revealed the close relationship between such hierarchies to the notion of tension and release (Bigand, 1993;.…”
Section: Tonal and Atonal Tensionmentioning
confidence: 73%
“…The current study suggests a view of harmonic expectation that is multifaceted and complex, and we can easily imagine various ways to expand our current approach to include further complexities. Previous work has investigated how parameters such as ''roughness'' and measures of harmonic distance (such as distance on the circle of fifths) interact with musical expectations (Bigand et al, 1996;Brown & Tan, 2021;Krumhansl, 1979), as well as how the metrical positioning of a harmonic event effects the cognition of that event (Dawe, Platt, & Racine, 1995;London, 1990London, , 2012Mirka, 2009;Prince, Thompson, & Schmuckler, 2009;Rosenthal & Hannon, 2016;White, 2017). Incorporating more potential parameters and endings into future behavioral and computational designs would provide insights into possible interactions between inversion, these parameters, and listeners' harmonic expectations.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…This being the case, then the occurrence of licks is potentially dependent on their placement in the temporal structure of the measure ( metrical position ). Certain temporal characteristics of the use of pitch have been investigated in previous research; for example, it has been demonstrated in several experiments that more stable pitches, according to models of tonal hierarchy, are associated with more stable beats, according to models of metrical hierarchy (Prince & Schmuckler, 2012; Verosky, 2019; White, 2017), but the role of metrical position in the use of licks deserves further consideration.…”
mentioning
confidence: 99%